PENDAMPINGAN PENGELOLAAN ARSIP PERPUSTAKAAN DESA GUNUNG SARI KECAMATAN TANJUNG SELOR KABUPATEN BULUNGAN - Kartini Maharani Abdul,; Iskandar, Iskandar; Wempi Feber,; Jimmy Nasroen,; Irsyad Sudirman,; Budi Mulyadi,; Masruri, Masruri; Syaini, Syaini; Isak Rapinadi Merang, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
There are problems in the management of the Gunung Sari Village library archives which are still messy and not well organized and the library's books are arranged and there is only one employee who manages the library archives. Based on these problems, it is considered important to assist in the management of library archives in Gunung Sari Village, Tanjung Selor District, Bulungan Regency, which is the only library managed directly by the Village Government and is a place for the community, especially people who are still in school, to gain knowledge by reading directly in the library that has been provided. provided by Gunung Sari Village. The method used in this service uses lecture techniques and training provided directly in the mentoring activities. Furthermore, the results obtained are improvements made in the management of the Gunung Sari Village Library archives, namely re-managing the library archives, classifying books and arranging them systematically on bookshelves which have their own categories to make it easier to find, as well as helping human resources